APPLICATION OF VASOPRESSIN ANALOGUE IN CAESAREAN SECTION IN WOMEN AT HIGH RISK OF BLEEDING - Яна Андреевна Парфенова; Наталья Владимировна Артымук; Оксана Николаевна Новикова; Нонна Марковна Шибельгут; Наталья Анатольевна Батина; Михаил Сергеевич Просветов; Василий Николаевич Паличев (The Publishing House Medicine and Enlightenment, 2022)
Aim - the aim of the study is to carry out a comparative assessment of clinical and anamnestic indicators and features of caesarean section surgery in patients with a high risk of developing intraoperative bleeding, delivered with and without the use of the vasopressor drug Terlipressin. Materials and methods. A retrospective case-control study of 92 women, with a high risk of developing intraoperative bleeding, delivered at the Belyaev Kuzbass Regional Clinical Hospital for 2020-2021 was conducted. The main group was 12 women who were injected intraoperatively into the thickness of myometry with the drug Terlipressin immediately after crossing the umbilical cord. The control group included 80 women operated without terlipressin. Statistical data processing was carried out using the computer program Microsoft Excel 2007. To compare the frequencies of qualitative features, the criterion χ2 was used. The level of statistical significance when testing the null hypothesis was taken as corresponding p < 0.05. Results. Patients who were administered terlipressin at caesarean section had a higher incidence of placental presentation and placenta accreta, i.e., initially belonged to the group of extremely high risk of obstetric bleeding. During caesarean section surgery, these patients were naturally statistically significantly more likely to undergo dressing of the descending branch of the uterine artery, application of compression sutures, additional administration of uterotonic preparations, tranexamic acid, colloidal solutions. The average blood loss in patients who received terlipressin was slightly higher than in the control group, however, no differences were found in the severity of blood loss, the frequency of massive blood loss was recorded in only one woman (8.3 %) who needed Cell Saver and hemotrasfusion. Conclusions. The analogue of vasopressin «Terlipressin» during caesarean section surgery is significantly more often used in patients of extremely high obstetric risk. Use of this preparation in combination with compression sutures and ligation of the descending branch of the uterine artery allows preventing massive blood loss. Further in-depth research is needed in this direction.